Mathematical Critical Thinking Ability and Adversity Quotient in Mathematics Learning: A Systematic Literature Review - Putra, Ari Limay Trisno; Fitriani, Namiyah; Noerzanah, Firda; Nadawiyah, Rabiatul (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2025)
This study aims to systematically review the literature discussing mathematical critical thinking skills and Adversity Quotient in the context of mathematics learning, with a focus on the ability conditions, indicators used, and a synthesis of research findings. The method used is Systematic Literature Review with reference to the PRISMA stages. Articles were obtained through searches on Google Scholar and SCOPUS databases using related keywords, then selected based on inclusion and exclusion criteria. The selected articles were analyzed descriptively-qualitatively. The results of the study indicate that students' mathematical critical thinking skills at various levels of education are generally in the low to moderate category, especially in the analysis, evaluation, and conclusion drawing indicators. The indicators of mathematical critical thinking skills used in the study are dominated by the Ennis and Facione framework, while the Adversity indicator Quotient generally refers to Stoltz 's CORE model which includes Control, Origin Ownership, Reach, and Endurance. Synthesis of findings shows that students with the highest level of Adversity Students with a higher AQQ tend to have better mathematical critical thinking skills, particularly in terms of persistence and reflection in solving mathematical problems. This study emphasizes the importance of developing mathematical critical thinking skills integrated with strengthening Adversity. Quotient in mathematics learning